Synthesis, structural characterization, density functional theory calculations, and antimicrobial, anticancer, and antimetastatic properties of nanosized heteroleptic complexes of cocaine/TMEDA with d‐block metal ions. (7th September 2021) - Abdallah, Abanoub Mosaad; Zaki, Nadia G.; Mahmoud, Walaa H.; El Kerdawy, Ahmed M.; Mohamed, Gehad G.
Abstract: In the field of transition metal chemistry, the development of transition metal‐based drugs for the treatment of diseases such as cancer or microbial infections with minimization of adverse effects and drug resistance constitutes an active area of research. Herein, eight novel nanosized heteroleptic complexes of cocaine/TMEDA with the formula [M(COC)(TMEDA)Cl y (OH2 ) z ]nCl· x H2 O (M = Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II), and Cd(II); COC = cocaine; TMEDA = N, N, N ′, N ′‐tetramethylethylenediamine, y = 1–2; z = 0–1; n = 0–1; and x = 0–2) were synthesized and structurally characterized via elemental analysis, molar conductivity, mass spectrometry, and spectroscopic and microscopic techniques. The thermal properties and kinetic thermodynamic parameters of the synthesized complexes were also studied. The geometry and electronic structures were investigated via density functional theory (DFT) calculations. The antiproliferative activity of the complexes on HepG‐2 and MCF‐7 cancer cell lines was quantified via MTT assay. The Fe(III) and Cd(II) complexes exhibited promising cytotoxic activities against the HepG‐2 and MCF‐7 cancer cell lines, respectively, with minimum effect on HFB4 human normal cells. Further molecular mechanistic studies were performed on the Cd(II) complex to inspect its influence on different cancer pathophysiology‐related processes in the MCF‐7 cell line including metastasis, apoptosis, and cellular oxidative stress and on the cellular levels of the human tumor suppressor nuclear proteins p21 and p27. The results revealed that the Cd(II) complex is a promising anticancer agent that acts through several molecular mechanisms with minimum effect on the normal cells and with additional antimetastatic properties. Furthermore, the antibacterial and antifungal activities of the prepared complexes were investigated. Abstract : Eight novel nanosized heteroleptic complexes of cocaine/TMEDA were synthesized and structurally characterized via different spectral and analytical tools. DFT and TD‐DFT calculations were conducted to investigate geometry optimization, electronic structure, and molecular electrostatic potential maps. The antiproliferative activity of the prepared complexes on the HepG‐2 and MCF‐7 cancer cell lines was studied. Further molecular mechanistic studies were performed on the Cd(II) complex to investigate its influence on the different processes related to cancer pathophysiology in the MCF‐7 cell line.